Membangun Proxy Server Dan Web Server Dengan Menggunakan Sistem Operasi Centos 5.6 Di Sekolah Menengah Teknologi Industri (SMTI) Padang - Kurniawan; Junaidi (Journal Of Informatics And Busisnes, 2024)
Web server is software that provides web services, web server using a protocol called HTTP. While the proxy server is a program that receives request from clients, such as a web browser or FTP client, and then forwards the request to the destination internet server. Through this proxy server, the client feels as though directly interact with the target’s internet server, or visited. The operating system used on the server in the form of Centos 5.6 which will serve as a proxy server and web server. Existing network at SMTI Padang is the network that has not been well managed. As internet access is slow due to the activities clients who often do excessive downloading. Whith the building of a proxy is solution of the problem that occurred in SMTI Padang.